2019
DOI: 10.14260/jemds/2019/327
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of Spleen

Abstract: BACKGROUND Spleen is the largest lymphoid organ playing a vital role in the defense mechanism of the body and performs a unique function of filtration of blood by phagocytes. We wanted to study the morphological variations and to compare the results with previous findings and to unearth the so far unnoticed features of the spleen. METHODS This is a descriptive study. 60 human cadaveric normal spleens were studied. The morphological features of the spleen such as shape, surfaces, poles, and measurements of bord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 4 publications
3
4
0
Order By: Relevance
“…The most common shape was the wedge shape followed by triangular, irregular, oval, and round shapes. The observation of wedge shaped spleen as the commonest shape is in agreement with the findings of many other studies in India, 6,10,[11][12][13][14][15] but differs from Srivani D et al 9 and Swargam N 16 who observed tetrahedral and triangular shapes respectively as the commonest shapes. The tetrahedral shaped spleen was not found in our study, but the round shaped spleen constituted 5.89% of the total of 34 spleens observed.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The most common shape was the wedge shape followed by triangular, irregular, oval, and round shapes. The observation of wedge shaped spleen as the commonest shape is in agreement with the findings of many other studies in India, 6,10,[11][12][13][14][15] but differs from Srivani D et al 9 and Swargam N 16 who observed tetrahedral and triangular shapes respectively as the commonest shapes. The tetrahedral shaped spleen was not found in our study, but the round shaped spleen constituted 5.89% of the total of 34 spleens observed.…”
Section: Discussionsupporting
confidence: 91%
“…The anomalous fissures were seen on both the diaphragmatic and visceral surfaces in the current study and Anusha D et al 15 reported similar findings. The anomalous fissures might be due improper fusion of the splenic nodules during development or mechanical pressure by the adjacent viscera.…”
supporting
confidence: 89%
See 3 more Smart Citations